Implikasi Program Literasi Perpustakaan Dalam Meningkatkan Minat Baca Peserta Didik Disekolah SMANegeri 1 Medang Deras Kabupaten Batu Bara - Lubis, Ikhwaniyah; Yusman; Parinduri, Sari Atika; Yusman, Yusman (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
Department of Islamic Religious Education, Islamic College of Tebingtinggi Deli. This study uses a qualitative descriptive approach with a field research study design. This study aims to determine the planning, implementation, and evaluation related to the Implications of the library literacy program in increasing students' reading interest in SMA Negeri 1 Medang Deras, Batu Bara Regency. This study obtains information by collecting data through observation, interviews, and documentation from primary and secondary data sources. Primary data comes from several informants as interview resource persons, namely the principal, class teachers, library staff and several students at SMA Negeri 1 Medang Deras, Batu Bara Regency. The data was analyzed using data reduction techniques, data presentation, and making conclusions/verification.            The research data was checked for validity by using extended observation, increasing persistence, triangulation and using reference materials. The results of this study indicate that 1) Literacy program planning in increasing students' reading interest in SMA Negeri 1 Medang Deras, namely: planning related to schedules, work programs/activities, methods, and supporting facilities and infrastructure in the literacy program. 2) Literacy program strategies in increasing students' reading interest in SMA Negeri 1 Medang Deras, namely: Providing special hours for students to read in the school library, motivating students about the importance of reading, arranging the layout of books in the library to attract students' interest in reading, making reading a habit before learning begins 3) Evaluation: Evaluation of the literacy program can be known based on student learning outcomes and report card grades.